Stunting Prevention through Training of Mothers in Processing Catfish into Dim Sum in Ranah Singkuang Village - Paramita, Irma Susan; Atasasih, Hesti; Hindratni, Findy (Sarana Ilmu Indonesia (salnesia), 2025)
Ranah Singkuang Village in Kampar Regency continues to face cases of stunting among toddlers, despite the local stunting prevalence rate being below the national target. One of the mitigation efforts involves utilizing local food sources, specifically catfish (Pangasius), as an accessible and affordable source of animal protein for the community. This Community Service Program aimed to improve the knowledge of mothers with toddlers through nutrition education and training in processing catfish into supplementary food in the form of dim sum. Evaluation through pre-test and post-test assessments indicated a significant improvement in mothers’ knowledge regarding stunting and nutrition. Additionally, training participants demonstrated adequate skills in preparing catfish-based dim sum. These findings suggest that educational activities and cooking demonstrations are effective in enhancing mothers’ knowledge and skills in utilizing catfish as supplementary food for toddlers.